2014
DOI: 10.17219/acem/37348
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation During Diabetes Therapy and the Potential Risk of Interactions

Abstract: Background. The classification of dietary supplements as foodstuffs promotes widespread access to them and increases the possibility of patients using them without being monitored. Unreasonable or excessive consumption of these preparations poses risks to type-2 diabetes mellitus (T2DM) patients (among others) because it may induce disturbances in glycemic control. The aim of this study was to assess the frequency of dietary supplementation among patients using anti-diabetic drugs and such patients' nutrient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The primary reason for undisclosed HDS use was unawareness of this concern. Additionally, over 70% of participants exposed to HDS had no awareness of drug-herb interactions [ 44 ]. As HDS use becomes more popular, physicians should consider HDS intake to be equally as important as that of conventional medication.…”
Section: Discussionmentioning
confidence: 99%
“…The primary reason for undisclosed HDS use was unawareness of this concern. Additionally, over 70% of participants exposed to HDS had no awareness of drug-herb interactions [ 44 ]. As HDS use becomes more popular, physicians should consider HDS intake to be equally as important as that of conventional medication.…”
Section: Discussionmentioning
confidence: 99%
“…Various nutritional factors such as magnesium, folic acid, vitamins B 12 and B 6 , and polyunsaturated fatty acids (PUFAs) appear to be significantly beneficial for patients with T2DM and CHD [9,10]. There is scarce information on the beneficial effects of selenium supplementation on metabolic status in patients with T2DM and CHD and the results are inconsistent.…”
mentioning
confidence: 99%
“…Regular consumption of MVT preparations as medical food for diabetics is common in developed countries. However, preclinical or clinical evaluation of such preparations is surprisingly limited in the literature [ 12 16 ]. To the best of our knowledge, none of the investigated and significantly altered genes in this study has been reported to show altered expression, either in healthy or in diabetic hearts in response to MVT-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MVT preparations appeared on the market as medical food for patients suffering from metabolic diseases including hyperlipidaemia, metabolic syndrome, and DM. However, the literature is limited and controversial on the potential beneficial effects of these complex preparations containing more than 3 components on disease progression [ 12 16 ]. We have recently shown that chronic treatment with a MVT preparation improved well-established diagnostic markers of DM such as fasting blood glucose, HbA1c, glucose tolerance, and serum insulin levels in male diabetic rats [ 14 ].…”
Section: Introductionmentioning
confidence: 99%